Bladder cancer. A retrospective analysis of the use of vinfluvin in real clinical practice - A. S. Zhabina; A. I. Novikov; F. V. Moiseenko; N. M. Volkov; E. O. Stepanova; E. V. Artemeva; N. H. Abduloeva; V. M. Moiseenko (Исследования и практика в медицине)
Purpose of the study. There is the generalized analysis of administration of vinflunine in real clinical practice in St.Petersburg Clinical Scientific and Practical Center of Specialized medical Care (oncological).Materials and methods. This analysis gathered 27 patients with urothelial carcinoma treated using this medicine in St.Petersburg Clinical Scientific and Practical Center of Specialized medical Care (oncological). We assessed efficacy, safety profile of vinflunine in this subset of patients.Results. Clinical efficacy of vinflunine (complete response + partial response + stable disease) was 51,86 %, one patient demonstrated complete response. Median of response duration accounts for 3,4 months. Adverse events were observed in 28,4 %, most of them were 1-2 grades. 2 patients stopped therapy due to adverse events.Conclusion. In our analysis vinflunine was more effective than in randomized clinical trial and other studies from real practice in Europe. Thus, confirm expediency to administer of vinflunine for metastatic urothelial carcinoma.